New material of Euroleptochromus tuberculatus Yin & Cai (Coleoptera: Staphylinidae: Scydmaeninae) in Eocene Baltic amber - Chen, Xin-Hui; Yin, Zi-Wei (Zootaxa, 2023)
The extinct members of the ant-like stone beetle supertribe Mastigitae are among the best studied groups of all fossil Scydmaeninae, and their evolutionary history can be traced from the latest Albian to the earliest Cenomanian through Miocene/Oligocene, with seven extinct genera being described (summarized in Jałoszyński, 2016; Jałoszyński & Perkovsky, 2016; Jałoszyński et al., 2018; Ross, 2019–2022 (list of Burmese amber taxa)).